Funding efficiency of science centers and technical innovations - Y. M. Akmaletdinova; P. A. Dudkina (Путеводитель предпринимателя)
The material in this article is devoted to issues related to the effectiveness of funding research centers and technical innovations. In the modern world, the development of innovation centers that influence the further development of the state and its economic growth is increasingly gaining popularity, so the issue of financing innovative ideas is considered relevant and important at the present time.